Evaluation of Pulsating Pressure and Emitter Position in Preventing Drip Emitters from Clogging - Fernandes, Caio Nascimento [UNESP] (2022)
Non-pressure compensating (Non-PC) emitters are employed mainly in drip irrigation systems due to their structural simplicity and low manufacturing costs; however, they present high sensitivity to physical obstruction, even when using filtration. This research aimed to analyze the effects of pulsating pressure, constant pressure, and water exit position in terms of preventing clogging in Non-PC drippers with a labyrinth system. The tests were performed on a test bench, and each treatment had 68 drippers (repetitions). Quartz sand was added to the irrigation water at a 500 mg L-1 concentration in two granulometric ranges (53-105 and 250-500 μm) to reproduce field conditions. The performance indicators were emitter flow rate (L h-1) and relative flow rate (qr). For the 250-500 μm granulometric range and the emitters positioned with the water exit facing downward, the 30 s constant pressure and 1 min pulsating pressure resulted in the obstruction of all emitters with only 2 h of operation. In the 53-105 μm granulometric range with the emitter hole facing downward, a pulsating pressure with a 1 min cycle was the most efficient at delaying emitter clogging, showing qr>75% during the first 16 h of operation. When the dripper exit was positioned facing upward in the most critical situation (constant pressure), no clogging was observed within the two granulometric ranges during the 40 h test. For this emitter model, which is widely applied in horticulture, a water exit facing upward is recommended to prevent clogging by suspended solid particles.